Mathematics Embedded in Culture: The Weaves of Batak Basketry - De Las Peñas, Ma. Louise (Archīum Ateneo, 2021)
A close look at the art of basket weaving of the Batak indigenous community in Palawan, Philippines, discloses the depth of mathematics present in the weaves of the baskets. Using white and black one-sided bamboo strips, Batak weavers are able to construct a basket of a given size that displays highly symmetric patterns. The presence of elaborate patterns in the baskets indicates masterful planning by the weaver and an inherent knowledge of algebraic and geometric principles even without formal training in mathematics.KEYWORDS: BATAK • BASKET • WEAVE • SYMMETRY • PATTERN